An assessment of the foliar heavy metal contamination in the Palabora Mining region - Kendall, Louise (My University, 2014)
This study was conducted in order to ascertain the levels of elemental concentrations in tree leaf and leaf litter samples collected in two areas at the Rio Tinto Palabora Mining Company. The elemental content in leaves from trees growing in the smelter plume deposition area and in the area around the main copper tailings was determined. The study will provide further insight into the extent of the contamination in these areas exhibiting high visible contamination and potentially high impacts. Sampling was carried out in November 2008, April 2011 and November 2011. A total of 135 leaf samples from three tree species (Lonchocarpus capassa, Colophospermum mopane and Euclea divinorum) were analysed, of which 74 samples were from the smelter plume deposition area, 51 samples were from the main copper tailings seepage area and 10 were leaf litter samples. Elemental concentrations in the leaves were measured and total percentages of C, H, N and S were determined. The highest concentrations of elements were found in the leaf litter samples from the smelter plume deposition area in 2008, with the average concentrations being: 1.57 ug/g of Ni, 9.44 ug/g of Bi, 16.3 ug/g of Pb, 110 ug/g of Mn, 122 ug/g of Ti, 483 ug/g of Al, 1463 ug/g of Cu, 2812 ug/g of S and 5611 ug/g of Fe. Element concentrations in trees varied with the tree species, higher levels were found in L. capassa and E. divinorum leaves than in C. mopane leaves. In the leaves analysed from the smelter plume deposition area the element concentrations decreased in the order S > Fe > Al > Cu > Mn > Ti > Pb > Ni > Bi. In the leaves from the Cu tailings seepage area the element concentrations decreased in the order S > Fe > Mn > Cu > Al > Ti > Ni > Bi > Pb. Significant differences were observed for the concentrations of certain metals and elements in the leaves between the three years (2008 to 2011) and between seasons (April to November). The concentrations generally decreased from 2008 to 2011and from April to November 2011. The findings from this study indicate that both of the high impact areas investigated are contaminated by the mining activities, with trees growing in the smelter plume deposition area showing higher contamination than trees in the Cu tailings seepage area. The leaves and leaf litter sampled in this study can be used as bioindicators of the contamination in this region.
Keywords: Pollution - South Africa - Palaborwa mining.; Leaves - Environmental aspects.; Metal - Environmental aspects.; Environmental pollution.